Overview of Blood Stocks and Demand During the COVID-19 Pandemic in Blood Donation Unit PMI Sleman Yogyakarta - Novita Widy Astuti; Nur'Aini Purnamaningsih; Tri Sunarsih (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2021)
The objective of this study were describe the stock and demand for blood during the Covid-19 pandemic at the Blood Donation Unit PMI Sleman Regency in 2019-2020 as well as efforts to meet the availability of blood stocks. This research was a quantitative descriptive study with a retrospective approach. The results showed that due to the Covid-19 pandemic, the amount of blood stock and demand at Blood Donation Unit PMI Sleman Regency increased. The number of blood stocks in 2019 before the Covid-19 pandemic was 11.500 blood bags with a demand for blood coming in as many as 11.487 bags. Meanwhile, the number of blood stocks in 2020 during the Covid-19 pandemic was 12.303 blood bags with a demand for blood coming in as many as 12.515 bags. So that during the Covid-19 pandemic taking place in 2020 as many as 212 requests for blood (1,69%) could not be fulfilled due to a lack of blood supply. Lack of blood stock caused by the reduced presence of donors due to the Covid-19 pandemic. Efforts to fulfill blood stock are carried out by improving services and supporting facilities.